Illuminance distributions, visual response and limits for conservation of exhibits in admiral Cheng Ho Gallery, Malaysia - Ahmad, Noraini; Sheikh Ahmad, Sabarinah; Talib, Anuar (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
This paper presents i) literature review of illuminance limits for conservation of exhibits; ii) pilot study on illuminance levels and distributions, air temperatures and relative humidity, RH and iii) survey results on visitors’ visual feedbacks on the exhibits’ conditions conducted at the Admiral Cheng Ho Gallery (Museum of History and Ethnography), Stadthuys, Melaka, Malaysia. Indicators for visual discomfort are observed from objectives ii and iii. The fieldwork was a pilot survey in the west facing gallery during high period of daylight distributions (14.00 -16.00hr) for a full week in March 2010. Results showed illuminance levels exceeded allowable exposure limits for some showcases. Measured air temperatures were much higher than accepted comfort range especially with opened windows in the afternoon and the RH levels were within the prescribed range. The survey identified the combination of natural daylight and artificial lighting deteriorated the exhibits’ conditions through fading, distortion, dirt and dust. The showcases were placed against and opposite the fully opened windows. Thus, the presence of sunlight, daylight and provision for external views in the gallery produced glare and veiling reflections problems on the glass showcases. These situations may demonstrate the need for proper maintenance and appropriate controlled shading system. The evaluation of daylight distributions may serve as future conservation measure for the exhibits.